Analysis of capillary water migration law of compacted loess in Ningxia - Cui, ZiZhi; Jing, Xin; Hao, JiaXing; Doh, Shu Ing (Pjoes, 2020)
Capillary water is the main cause of freezing damage and collapsible damage of compacted loess. Therefore, researching capillary water migration law of compacted loess is the key to solve various damage in the infrastructure construction of loess. Different regions have different climatic conditions, which make the physical and mechanical properties of the loess is different. In order to reveal the capillary water migration law of compacted loess in Ningxia, the moisture migration law of compacted loess with different degrees of compaction was studied by using standpipe method. The results show that the migration rate of capillary water is rapid at the early stage and gradually became slower with the increase of time, which is negatively related to the degree of compaction and migration height. The maximum migration height of capillary water increases exponentially with the increase of compactness. Migration rate and migration height of capillary water are related to capillary water potential, gravitational potential, and pipe-resistance of capillary. In this study, the relational equation can predict capillary water distribution and the migration height of compacted loess was newly established. This equation can also provide a reference to reduce various damage and freeze-thaw effect in compacted loess.